Inclusive and Responsive Strategies for Advancing the Human Resource Paradigm Toward Indonesia's Golden Vision - Ilham Tahier; Andi Nadirah; Burhanuddin Harahap (Goodwood Publishing, 2026)
Purpose: The transformation of human resources (HR) towards the vision of Golden Indonesia 2045 requires a strategic approach to human resource management that is both flexible and effective. Research Methodology: A structured questionnaire with a Likert scale was used to collect quantitative data. The research data of 73 students majoring in management at the University of Muhammadiyah Palopo were processed using statistical analysis based on partial least squares structural equation modeling (SEM) with the SmartPLS application. This research was conducted from March to April 2025. Results: This study examines how Generation Z perceives the role of Inclusive HR (X1) in shaping organizational phenomena, revealing that this variable does not exert a significant or beneficial influence on the paradigm of Indonesia's golden vision (Y). Meanwhile, the Responsive HR (X2) research variable has been shown to have a positive and significant impact on the Golden Indonesia HR Paradigm (Y). Furthermore, the Impactful HR variable (X3) has a significant and positive effect on the Golden Indonesia HR Paradigm (Y). Conclusions: The higher the level of responsiveness of HR in dealing with external changes, such as digital transformation, demographic shifts, and labor market dynamics, the greater its contribution to the direction and strategic framework of national human resource development. Limitations: This indicates that Indonesia's HR transformation requires a holistic HR approach: inclusive in engagement, responsive to change, and having a real impact on organizations and society. Contributions: For HR practitioners and policymakers, these findings mean that HR must become an agent of strategic change, training programs, reward systems, and talent development must be directly related to national human resource development macro targets, and HR must evaluate the social impact of policies, such as inclusivity and product development.